2005
DOI: 10.1084/jem.20042491
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in targeting of class switch recombination sites in mice that lack μ switch region tandem repeats or Msh2

Abstract: The mechanisms that target class switch recombination (CSR) to antibody gene switch (S) regions are unknown. Analyses of switch site locations in wild-type mice and in mice that lack the Sμ tandem repeats show shifts indicating that a 4–5-kb DNA domain (bounded upstream by the Iμ promoter) is accessible for switching independent of Sμ sequences. This CSR-accessible domain is reminiscent of the promoter-defined domains that target somatic hypermutation. Within the 4–5-kb CSR domain, the targeting of S site loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…In fact, the level of residual switching observed in APE1-deficient cells in this study is remarkably similar to that observed in cells deficient in UNG2. MMR has been shown to be particularly important when core switch repeats were deleted and overlapping AID hot spots were scarce (10,32,33). Among the MMR factors, the MutL␣ (MLH1/ PMS2) complex has been reported to possess a latent endonuclease activity that is activated upon mismatch recognition (34).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the level of residual switching observed in APE1-deficient cells in this study is remarkably similar to that observed in cells deficient in UNG2. MMR has been shown to be particularly important when core switch repeats were deleted and overlapping AID hot spots were scarce (10,32,33). Among the MMR factors, the MutL␣ (MLH1/ PMS2) complex has been reported to possess a latent endonuclease activity that is activated upon mismatch recognition (34).…”
Section: Discussionmentioning
confidence: 99%
“…AID only deaminates C's when these are located in single-stranded DNA (4,25,44). CSR at the downstream switch regions occurs within the switch repetitive regions, and recom-bination at S can sometimes occur upstream (35%) or downstream (8%) of the S switch repeats (8,(21)(22)(23). Given that AID requires single-stranded DNA, a key question concerns how any single strandedness is exposed within the switch regions (33).…”
mentioning
confidence: 99%
“…S tandem repeats that are rich in RGYW/WRCY undergo breakage and mediate CSR independently of Msh2. In contrast, DNA breakage in sequences flanking the S tandem repeats requires Msh2 to allow recombinational joining and CSR to unfold (68,69), implicating a more significant role of MMR proteins in S-S DNA recombination events involving sequences with scarcity of RGYW/ WRCY (68). Thus, Mlh3 deficiency shifts the S␥ breakpoints of S-S␥ to RGYW/WRCY, implicating a significantly role of Mlh3 in facilitating S-S recombination events outside RGYW/WRCY.…”
Section: Discussionmentioning
confidence: 95%